Efficacy Maintained When Transitioning Directly from TNF Inhibitor to Tofacitinib in RA - Kuznar, Wayne (MD Conference Express, 2013)
Patients with rheumatoid arthritis (RA) who transition directly from adalimumab to tofacitinib maintained a clinical response. This article presents results from the open-label extension Oral Rheumatoid Arthritis Phase 3 Trials Sequel study [ORAL; NCT00413699] of the randomized, double-blind, placebo-controlled ORAL Standard study in which the two treatments were compared in patients with active RA [NCT00853385].